Soluble Adhesion Molecules During Ex Vivo Lung Perfusion Are Associated With Posttransplant Primary Graft Dysfunction. Issue 5 (1st February 2017) - Hashimoto, K.; Cypel, M.; Kim, H.; Machuca, T. N.; Nakajima, D.; Chen, M.; Hsin, M. K.; Zamel, R.; Azad, S.; Waddell, T. K.; Liu, M.; Keshavjee, S.
Abstract : Ex vivo lung perfusion (EVLP) enables assessment of marginal donor lungs for transplantation. We aimed to discover biomarkers in EVLP perfusate that could predict development of primary graft dysfunction (PGD). From September 2008 to August 2013, 100 clinical EVLPs were performed. Eleven patients developed PGD grade 3 within 72 h after transplant. The non‐PGD group consisted of 34 patients without PGD grade 3. Nonbilateral lung transplants or transplant after extracorporeal life support were excluded from analyses. Soluble intercellular adhesion molecule 1 (sICAM‐1), soluble VCAM‐1 (sVCAM‐1), and soluble E selectin (sE‐selectin) levels, as markers of endothelial activation, were measured in the perfusate of EVLP by enzyme‐linked immunosorbent assay and were correlated with clinical outcome. Levels of sICAM‐1 at 1 h and sVCAM‐1 at 1 and 4 h were significantly higher in the PGD group compared with the non‐PGD group. The sE selectin levels were not statistically different between the study groups. Higher levels of sVCAM‐1 at 1 and 4 h were statistically significantly associated with PGD either alone or after adjustment for other PGD risk factors. These adhesion molecules may help identify donor lungs at higher risk of PGD during EVLP. Abstract : Soluble adhesion molecules in ex vivo lung perfusate are biomarkers associated with post–lung transplant primary graft dysfunction.